2020
DOI: 10.1109/access.2020.3037998
|View full text |Cite
|
Sign up to set email alerts
|

Design Sustainability of Reconfigurable Machines

Abstract: This paper presents the sustainability assessment for reconfigurable machines based on cosine similarity measures and Euclidean distances. The methodology entails the application of four peculiar sustainability indicators (Reconfigurability, Manufacturing, Functionality, and Life Cycle Analysis) that are suitable for reconfigurable machines alongside the traditional sustainability indicators (Environmental, Social, and Economic). An index relating chart approach is proposed for determining the indices of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The common aim of the models proposed in these papers is to reduce costs, whereas it is found that if achieving this aim, an economic sustainability is fulfilled. The cost reduction is specified to certain areas, for instance maintenance [26,28,39,43], inventory [38,39], transportation [22,25,35], investment [21,43], manufacturing [19,29,31,38,39], and reconfiguration cost [22,26,29,31,32,35,39]. The latter can be recognized as a fairly exclusive cost for RMS, on the basis that this type of manufacturing system leads to more frequent system-, machine-and tool changes.…”
Section: Economic Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The common aim of the models proposed in these papers is to reduce costs, whereas it is found that if achieving this aim, an economic sustainability is fulfilled. The cost reduction is specified to certain areas, for instance maintenance [26,28,39,43], inventory [38,39], transportation [22,25,35], investment [21,43], manufacturing [19,29,31,38,39], and reconfiguration cost [22,26,29,31,32,35,39]. The latter can be recognized as a fairly exclusive cost for RMS, on the basis that this type of manufacturing system leads to more frequent system-, machine-and tool changes.…”
Section: Economic Sustainabilitymentioning
confidence: 99%
“…In total, 7 of the reviewed papers included social sustainability in their research. Factors such as employee health and safety [3,17,27,39], training and education [25,27,39], and ethical and legal following [19,27,39] are recurrently discussed in multiple papers as having a connection to RMS. Some authors are describing social sustainability in an imprecise term and focus on the general factors which a production system can lead to, as for instance in Kurniadi & Ryu [38] where the ability to reconfigure a manufacturing system leads to the possibility to match requirements in terms of quantity and products to changing demands.…”
Section: Social Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the fact that the design features that are usually applied as criteria in the decision process are of different dimensions and units, researches have introduced the theory of fuzzy membership functions and rough numbers in the MADM models. The introduction of the fuzzy and rough number theories is to cater for the multifarious units and dimensions of the design features and ensure that the decision process is unprejudiced and there is no allocation of crips value to weights of the design features of different units and dimensions or performance of the design concepts in the decision matrix [17]. Depending on the nature and objectives of the decision process and the complexity of the design features, Triangular Fuzzy Number (TFN) and Trapezoidal Fuzzy Number (TrFN) has been applied as membership functions in different MADM models in order to proffer solution in the decision process of selecting optimal conceptual design [18].…”
Section: Introductionmentioning
confidence: 99%
“…The examples of machine tools include; lathe, drill press, milling machine, screw machine, etc as depicted in Figure 1 . The machines tools can further be classified into dedicated machine tools ( Landers et al., 2001 ; Mayr et al., 2012 ; Chanal et al., 2007 ; Xu and Newman, 2006 ; de Lacalle and Mentxaka 2008 ; Koren, 2006 ; Valdes et al., 1997 ; Huang et al., 2010 ; Bringmann et al., 2014 ), Flexible machine tools ( Browne et al., 1984 ; Stecke, 1985 ; Mori and Fujishima 2009 ; Kostal &Velisek 2010 ElMaraghy, 2005 ; Patpatiya et al., 2021 ; Cook et al., 2020 ; Oshel et al., 2020 ) and Reconfigurable machine tools ( Ding et al., 2021 ; Xing et al., 2021 ; Kumar et al., 2021 ; Mahmoodjanloo et al., 2020a , Mahmoodjanloo et al., 2020b ; Huang et al., 2020 ; Ming et al., 2020 ; Bruzzone et al., 2020 ; Wang et al., 2020 ; Wang et al., 2018 ; Gadalla and Xue 2018 ; Olabanji and Mpofu 2020 ; Murena et al., 2017 ; Battaïa et al., 2017 ). The classification of machine tools is shown in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%